Novel Viologen Derivative Based Uranyl Coordination Polymers Featuring Photochromic Behaviors. Issue 71 (4th December 2017) - Hu, Kong‐Qiu; Wu, Qun‐Yan; Mei, Lei; Zhang, Xiao‐Lin; Ma, Lei; Song, Gang; Chen, Di‐Yun; Wang, Yi‐Tong; Chai, Zhi‐Fang; Shi, Wei‐Qun
Abstract: A series of novel uranyl coordination polymers have been synthesized by hydrothermal reactions. Both complexes1 and2 prosess two ipbp − ligands (H2 ipbpCl=1‐(3, 5‐dicarboxyphenyl)‐4, 4′‐bipyridinium chloride), one uranyl cation, and two coordination water molecules, which can further extend to 2D networks through hydrogen bonding. In complex1, two sets of equivalent nets are entangled together, resulting in a 2D + 2D → 3D polycatenated framework. In complex2, the neighbouring equivalent nets interpenetrate each other, forming a twofold interpenetrated network. Complexes3 and4 are isomers, and both of them are constructed from (UO2 )2 (OH)2 dinuclear units, which are connected with four ipbp − ligands. The 3D structures of complexes3 and4 are similar along the b axis. Similar to other viologen‐based coordination polymers, complexes3 and4 exhibit photochromic and thermochromic properties, which are rarely observed in actinide coordination polymers. Unlike the monotonous coordination mode in complexes1 –4, the ipbp − ligands feature a μ3 ‐bridge through two kinds of coordination modes in complex5 . Notably, complex5 presents a unique example in which terminal pyridine nitrogen atom is involved in the coordination. Abstract : A series of novel uranyl complexes were synthesized based on viologen derivative ligand by altering pH adjusters (HNO3, NaOH, triethylamine, DMF). Both complexes3 and4 exhibit photochromic properties, which are rarely observed in actinide coordination polymers.